Suvarnaprashana Samskar: A Literary Review - Chouhan, Dinesh C; Sharma, Punita; Ajay3 (International Research Journal of Ayurveda & Yoga, 2021)
Suvarnaprashana described by Acharya Kashyapa, the main pioneer of Kaumarbhritya (pediatrics). Suvarnaprashana is intended to boost memory, intelligence and immunity in infants. It is one of the oldest applications of gold nano medicine. Suvarnaprashana means to administer Suvarna Bhasma with the help of honey, Ghrita and some herbal medicines. Suvarnaprashana has been extensively described in main reference books i.e. Brihatrayi Granthas, Sushruta, Vagbhata, Kashyapa has mentioned its uses in detail. Suvarnaprashana has been traditionally practiced across India for child growth and memory enhancement and also to promote longevity. Suvarnaprashana is such Rasayana mentioned in Ayurveda to promote immunity and memory of children. Despite their efficacy, these age old therapies were discouraged, sidelined and almost forgotten during the colonial era and even after freedom. Through this article we make an effort to enlighten and reestablish the forgotten science.